2009
DOI: 10.2147/tcrm.s4029
|View full text |Cite
|
Sign up to set email alerts
|

Animal-derived surfactants for the treatment and prevention of neonatal respiratory distress syndrome: summary of clinical trials

Abstract: Introduction: Available literature suggests that the advantage of animal-derived surfactants over fi rst-generation synthetic agents derives from the presence of surface-active proteins and their phospholipid content. Here we summarize the results of clinical trials comparing animalderived surfactant preparations with other animal-derived surfactants and with both fi rst-and second-generation synthetic surfactants. Methods: Published clinical trials of comparisons of animal-derived surfactants were summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Overall study findings are consistent with a comparative effectiveness study of on-label surfactant that found no significant differences in air leak syndrome, BPD, or death among the three surfactants [ 17 ]; three efficacy trials that identified no significant differences in mortality or oxygen requirement at 36 weeks [ 20 23 ]; and another study, in which poractant alfa compared to beractant was associated with nonsignificant trends towards lower death and/or, BPD in infants 24–29 weeks GA [ 6 ]. In contrast to our results, prior studies identified significant benefits to poractant alfa [ 6 , 7 , 9 ]; but some observed outcomes appear due to differences in dosing [ 9 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…Overall study findings are consistent with a comparative effectiveness study of on-label surfactant that found no significant differences in air leak syndrome, BPD, or death among the three surfactants [ 17 ]; three efficacy trials that identified no significant differences in mortality or oxygen requirement at 36 weeks [ 20 23 ]; and another study, in which poractant alfa compared to beractant was associated with nonsignificant trends towards lower death and/or, BPD in infants 24–29 weeks GA [ 6 ]. In contrast to our results, prior studies identified significant benefits to poractant alfa [ 6 , 7 , 9 ]; but some observed outcomes appear due to differences in dosing [ 9 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 82%
“…Compared to beractant, calfactant has higher phospholipid content (95% vs 84%) and a greater SP-B concentration (5.4ug/umol vs 1.3ug/umol), suggesting improved surfactant effect [ 35 ]. In contrast, poractant (Curosurf ® ) is extracted from minced porcine lungs and undergoes a series of purification procedures by centrifuge to remove neutral lipids [ 10 ]. SP-B and SP-C are the only two protein types present [ 36 ].…”
Section: Biochemical Background Of Surfactant Analoguesmentioning
confidence: 99%
“…With the various natural surfactant subtypes available in the market, trials have sought to compare the efficacy of these surfactants (Table 3 ). A meta-analysis [ 10 ] identified three trials comparing beractant to calfactant [ 46 - 48 ], while four trials compared beractant to poractant [ 49 - 52 ]. No trials evaluated the efficacy of calfactant versus poractant.…”
Section: Comparative Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is induced by the lack of pulmonary surfactant (PS), 1 , 2 accounting for 50%-70% of premature deaths. 3 Its main pathogenesis is alveolar collapse due to immature pulmonary development of neonates and insufficient PS secretion, and its clinical manifestations include progressive dyspnea and respiratory failure shortly after birth. PS is a natural mixture derived from porcine lung or bovine pulmonary homogenate with phospholipids and specific proteins as the main ingredients, containing 41% to 48% of lecithin and 51% to 58% of other phospholipids and 1% of hydrophobin.…”
Section: Introductionmentioning
confidence: 99%